An integrated model for predicting atmospheric status in a sealed mine area - Cheng, Jianwei; Luo, Y. (2011)
Methane and coal dust explosions are the most feared hazards in the coal industry worldwide. A majority of these explosions were originated from or around the sealed areas. According to statistics, nearly all coal mine explosions initially started with the ignition of combustible gases such as methane, carbon monoxide, etc. However, due to inaccessible to the sealed area, predicting the gas composition change pattern and determining the explosibility of the gas-air mixture in a sealed volume become a challenge for mining engineers. In this paper, the most important factors to control the atmosphere compositions in a sealed area have been in detail analyzed. Based on these considerations, a mathematical model is proposed to predict the compositions changes in a sealed volume. In additional, the modified Coward's method is developed to check the explosibility of mine atmosphere, and new defined safety factor can also easily help the users understand the mine atmospheric status. Finally, the application of the integrated computer model in managing the mine sealed atmosphere is also discussed.